2018
DOI: 10.1186/s12974-018-1363-6
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and anti-oxidant mechanisms of an MMP-8 inhibitor in lipoteichoic acid-stimulated rat primary astrocytes: involvement of NF-κB, Nrf2, and PPAR-γ signaling pathways

Abstract: BackgroundRecent evidence suggests that reactive astrocytes play an important role in neuroinflammation and neurodegenerative diseases. Thus, controlling astrocyte reactivity has been suggested as a promising strategy for treating neurodegenerative diseases. In the present study, we investigated whether a matrix metalloproteinase (MMP)-8 inhibitor, M8I, could control neuroinflammation in lipoteichoic acid (LTA)-stimulated rat primary astrocytes.MethodsThe effects of M8I on the expression of inducible nitric ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 50 publications
1
30
0
Order By: Relevance
“…Age-up genes in astrocytes, C4b, involved in synapse elimination [48]; Snca and Sncg, 2 genes related to Parkinson's disease pathogenesis [49] that also play several roles in synaptic activity, such as regulation of synaptic-vesicle trafficking and subsequent neurotransmitter release [50,51], suggesting that astrocytes play a critical role in synapse elimination and synaptic transmission. Spock3 and Timp4, encode proteins that participate in inhibiting matrix metalloproteinases (MMPs) involved in the degradation of the extracellular matrix [52], and the other genes encode proteins that inhibit lipoteichoic acid-induced NF-κB, MAP kinase, and Akt activities [53] and decrease the invasion and metastasis of tumor cells in the brain [54]. Pcsk1n, an inhibitor of prohormone convertase 1 that regulates the proteolytic cleavage of neuroendocrine peptide precursors [55].…”
Section: Discussionmentioning
confidence: 99%
“…Age-up genes in astrocytes, C4b, involved in synapse elimination [48]; Snca and Sncg, 2 genes related to Parkinson's disease pathogenesis [49] that also play several roles in synaptic activity, such as regulation of synaptic-vesicle trafficking and subsequent neurotransmitter release [50,51], suggesting that astrocytes play a critical role in synapse elimination and synaptic transmission. Spock3 and Timp4, encode proteins that participate in inhibiting matrix metalloproteinases (MMPs) involved in the degradation of the extracellular matrix [52], and the other genes encode proteins that inhibit lipoteichoic acid-induced NF-κB, MAP kinase, and Akt activities [53] and decrease the invasion and metastasis of tumor cells in the brain [54]. Pcsk1n, an inhibitor of prohormone convertase 1 that regulates the proteolytic cleavage of neuroendocrine peptide precursors [55].…”
Section: Discussionmentioning
confidence: 99%
“…Tert-butylhydroquinone (tBHQ) enhanced angiogenesis and astrocyte activation through Nrf2 pathway in mice with permanent distal middle cerebral artery occlusion (dMCAO) [ 312 ]. tBHQ significantly reduced the infarct volume, enhanced post-stroke angiogenesis and astrocytic endfeet covered ratio in the peri-infarct area [ 312 ].…”
Section: The Therapeutic Impact: a Glial Avenue For Nigrostriatal Resmentioning
confidence: 99%
“…Tert-butylhydroquinone (tBHQ) enhanced angiogenesis and astrocyte activation through Nrf2 pathway in mice with permanent distal middle cerebral artery occlusion (dMCAO) [ 312 ]. tBHQ significantly reduced the infarct volume, enhanced post-stroke angiogenesis and astrocytic endfeet covered ratio in the peri-infarct area [ 312 ]. The Nrf2/HO-1/VEGF pathway was activated by tBHQ in the angiogenesis process, but not in Nrf2 −/− mice, where the Nrf2 deficiency blocked the effects of tBHQ on angiogenesis process and neurological recovery indicating a beneficial effect of activating Nrf2 pathway after cerebral ischemia [ 312 ].…”
Section: The Therapeutic Impact: a Glial Avenue For Nigrostriatal Resmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, individual gene expression analysis suggested that certain genes involved in PD inflammation were upregulated in DJ-1 −/− mice. The Poly(ADP-ribose) polymerase family, member 1 (Parp1) (p = 0.03) and Matrix metallopeptidase-8 (Mmp-8) (p = 0.01) genes which are involved in microglia and astroycytes inflammation [65][66][67] were significantly upregulated in DJ-1 −/− mice in the mid brain regions (Fig. 6d).…”
Section: Increased Inflammatory Genes Related To Pd In Dj-1 −/− Mice mentioning
confidence: 99%